2023
DOI: 10.1101/2023.10.01.558881
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

DNA i-motif levels are overwhelmingly depleted in living human cells: insights from in-cell NMR

Pavlína Víšková,
Eva Ištvánková,
Jan Ryneš
et al.

Abstract: I-Motifs (iM) are non-canonical DNA structures potentially forming in accessible, single-stranded, cytosine-rich genomic regions, with regulatory roles. Chromatin, protein interactions, and intracellular properties seem to govern iM formation at sites with i-motif formation propensity (iMFPS) in human cells, yet their specific contributions remain unclear. Using in-cell NMR with oligonucleotide iMFPS models, we monitored iM-associated structural equilibria in asynchronous and cell cycle-synchronized HeLa cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…In line with this hypothesis, a recent in-cell NMR study by Trantirek and coll. demonstrated that iM-forming sequences with pH T < 7 are predominantly unfolded in cells, suggesting that only a minor fraction of iM-forming sequences could form iM structures in physiological conditions (39).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with this hypothesis, a recent in-cell NMR study by Trantirek and coll. demonstrated that iM-forming sequences with pH T < 7 are predominantly unfolded in cells, suggesting that only a minor fraction of iM-forming sequences could form iM structures in physiological conditions (39).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the high number of iMab peaks observed by Richer and coll. in sequences with pHT < 7 are predominantly unfolded in cells, suggesting that only a minor fraction of iM-forming sequences could form iM structures in physiological conditions (39).…”
Section: B a Imab Unfolds Im Structures In Bulk-fret Experimentsmentioning
confidence: 99%